1992
DOI: 10.3354/meps080089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of natural ultraviolet radiation on rates of photosynthesis and on specific marine phytoplankton species

Abstract: Natural phytoplankton populations from both Antarctic and tropical waters were exposed to solar radiation to determine the effects of ultraviolet radiation (UVR) on rates of photosynthesis. Radiation in the UV-A region (320 to 400 nm) was responsible for over 50 % of the total inhibition due to UVR, with less than 50 % due to UV-B (280 to 320 nm). Wavelengths c305 nm, which is the spectral region most enhanced under conditions of low ozone concentrations in the atmosphere, accounted for only 15 to 20% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
169
3
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(187 citation statements)
references
References 19 publications
12
169
3
3
Order By: Relevance
“…Previous studies [7,18,[40][41][42][43] have shown that solar UVR can significantly inhibit photosynthesis of aquatic organisms in short time scales (i.e., less than a day). Nevertheless, cells can have different mechanisms to cope with the excessive solar radiation energy in the short-term scale; for example, photoprotection has been shown to be very effective in many algae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [7,18,[40][41][42][43] have shown that solar UVR can significantly inhibit photosynthesis of aquatic organisms in short time scales (i.e., less than a day). Nevertheless, cells can have different mechanisms to cope with the excessive solar radiation energy in the short-term scale; for example, photoprotection has been shown to be very effective in many algae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, most action spectra of the inhibitory effects of UV radiation on photosynthesis indicate that UVA wavelengths are effective (e.g. Jones & Kok, 1966;Cullen eta]., 1992; Helbling et aI., 1992) and, when allowance is made for the higher irradiances at UVA than at UVB wavelengths, account for observations that more than 50% of the inhibition of photosynthesis in phytoplankton caused by solar radiation is due to UVA (Helbling et al, 1992). A recent study of the effects of sunlight on photosynthesis and chlorophyll fluorescence in the green macroalga Ulva (Herrrnann et al, I995) also indicated that the removal of UVB wavelengths had a relatively small effect on the degree of photoinhibition, so that the results reported here are not atypical.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the effects of sunlight on photosynthesis and chlorophyll fluorescence in the green macroalga Ulva (Herrrnann et al, I995) also indicated that the removal of UVB wavelengths had a relatively small effect on the degree of photoinhibition, so that the results reported here are not atypical. The ecological significance of the relatively high effectiveness of UVA wavelengths is that thinning of the ozone layer will have little effect on these responses because the irradiance of wavelengths longer than 330 nm is almost independent of ozone concentration (Helbling et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations